Development of Coastal Tourism to Increase People's Economic Activities (Study on the Community Around Namalatu Beach of Latuhalat Country) - Lisa Tehupuring (CV. Rayyan Dwi Bharata, 2023)
This research is a qualitative descriptive research that aims to find out how to develop coastal tourism to improve the economy of the people around Namalatu Beach, Negeri Latuhalat. This research was carried out at Namalatu Negeri Latuhalat Beach Tourism Object, Ambon City. Primary data collection was carried out through interviews with a number of informants who were directly involved in the Namalatu Beach Tourism Object. The results of this study indicate that the development of coastal tourism to improve the people's economy is not only the responsibility of coastal communities but also good support from the government as a provider of facilities as well as interdependence and cooperation between the government and the community to develop better local tourism objects so that they can improve the economy of the community around the tourist attraction and also increase regional income.